(untitled) (Journal of Technology and Operations Management, 2017)
As manufacturing flexibility has been purported as an unconventional manufacturing approach in safeguarding competitive advantage, this research was proposed to investigate the impact of manufacturing flexibility on profitability in the context of manufacturing industry in Malaysia. The dimensions of manufacturing flexibility were mix flexibility, new product flexibility, labor flexibility, machine flexibility, material handling flexibility, routing flexibility and volume flexibility. Impacts of manufacturing flexibility on profitability have been tested using cross sectional study employing survey methodology conducted within five manufacturing industries in Malaysia. Data obtained from returned questionnaires were analysed using regression analyses. Findings of regression analyses provided support that manufacturing flexibility has positive and significant impact on profitability. In other words, manufacturing flexibility improves profitability. In conclusion, this research contributes to knowledge gaining regarding the concept of manufacturing flexibility and its impacts.